2014
DOI: 10.1002/bjs.9528
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of the National Health Service abdominal aortic aneurysm screening programme in England

Abstract: BackgroundImplementation of the National Health Service abdominal aortic aneurysm (AAA) screening programme (NAAASP) for men aged 65 years began in England in 2009. An important element of the evidence base supporting its introduction was the economic modelling of the long-term cost-effectiveness of screening, which was based mainly on 4-year follow-up data from the Multicentre Aneurysm Screening Study (MASS) randomized trial. Concern has been expressed about whether this conclusion of cost-effectiveness still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
1
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 27 publications
(41 reference statements)
4
104
1
1
Order By: Relevance
“…If AAA screening in 65-year-old men is cost-effective down to a prevalence rate as low as 0⋅35 per cent 39 , AAA screening also may be cost-effective in 70-year-old women, especially as the AAA rupture rate in women is about four times that in men for a given AAA diameter 40 . Indeed, a modelling study from Sweden 41 has already suggested that AAA screening for older women would be cost-effective, based on an AAA prevalence of 1⋅1 per cent in 65-year-old women.…”
Section: Discussionmentioning
confidence: 99%
“…If AAA screening in 65-year-old men is cost-effective down to a prevalence rate as low as 0⋅35 per cent 39 , AAA screening also may be cost-effective in 70-year-old women, especially as the AAA rupture rate in women is about four times that in men for a given AAA diameter 40 . Indeed, a modelling study from Sweden 41 has already suggested that AAA screening for older women would be cost-effective, based on an AAA prevalence of 1⋅1 per cent in 65-year-old women.…”
Section: Discussionmentioning
confidence: 99%
“…31 to 51) per cent)1, and is highly cost‐effective2. As a result, AAA screening in men aged 65 years was fully implemented across England and Wales in 2013, and is now established across the UK.…”
Section: Introductionmentioning
confidence: 99%
“…The long latent period between development of AAA and rupture offers an opportunity for screening which has been shown to reduce AAA-related mortality in men by detecting aneurysms prior to rupture and offering elective surgical repair to prevent rupture (2). Screening reduces AAA-related mortality by 50% and has been shown to be cost effective, even at low AAA prevalence rates (2)(3)(4). Nationwide AAA screening programmes have subsequently been introduced across the United Kingdom (UK), Sweden, in some regions of Denmark and in the United States (US) Veterans' Association.…”
Section: Introductionmentioning
confidence: 99%